STRATEGI GURU SEJARAH DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN SEJARAH DI SMAN 10 PEKANBARU (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2014)
From the observation that the author did in SMAN 10 Pekanbaru, known to manystudents from grade 1 to grade 3 is less interested in the lessons of history, because they lackprofessional teachers, especially teachers of history. This has led to interest students learn thehistory that led to the decline in student achievement, especially on the subjects of history. Toachieve the goal of learning is usually a teacher to choose one or more of teaching and learningstrategies. Where the strategy can be achieved when factors such as: the material being taught,teachers and students must actively use the role, there are certain social relations, types ofactivitiesdone, and facilities available.Keywords: Strategy Guru, Interest in Learning.